HYPERSPIRITUALITY OF MUSLIM TEENS LEARNING RELIGION ON THE INTERNET ERA - Sulaeman, Mubaidi; Ahmad Muttaqien; Ali, Jan A. (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2024)
This study investigates three key questions: how Muslim youth interpret religion in the Internet era, how the Internet influences and constructs it, and how religion is conceptualized. This is a qualitative study. The data was gathered through in-depth interviews, observations, and documentation. This study comprised 71 Muslim teens aged 17 to 21 from Kediri Regency who were chosen for their extensive usage of the Internet to explore Islam. The analysis involved data reduction, visualization, and conclusion. Data analysis techniques included descriptive, analytical, and interpretative approaches. The study's findings revealed that Muslim teenagers who learn Islam online experience hyperspirituality due to hypersemiotics. False indications and incomplete learning due to ignorance of Islamic religious research should lead to a nihilistic interpretation of Islam. Teens are deceived by the ideology driving religious information on the Internet, which they believe is neutral. Anti-ideological ideologies undoubtedly serve ideological goals. As a result, they incorrectly feel that the lack of dogma in online Islamic education prevents them from achieving their primary purpose.